EKSPERIMENTASI MODEL PROBLEM POSING TIPE WITHIN SOLUTION POSING, TIPE PRE SOLUTION POSING DAN TIPE POST SOLUTION POSING PADA PEMBELAJARAN MATEMATIKA DITINJAU DARI KEMAMPUAN PENALARAN SISWA KELAS VIII SMP NEGERI DI KABUPATEN BANJARNEGARA - Santosa, Farah Heniati; Usodo, Budi; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: This aims of the research were to determine the effect of the learning models on the learning achievement in mathematics viewed from reasoning ability of thr students. The learning models compared were the Problem Posing model type: Within Solution Posing, Pre Solution Posing, Post Solution Posing and the direct learning model. This research used the quasi experimental research method with the factorial design of 4x3. The population of the research was all students in Grade VIII of Junior Secondary Schools of Banjarnegara Regency. The samples of the research were chosen by using the stratified cluster random sampling technique and consisted of 316 students. The instruments used to collect the data were the test of mathematics achievement and test of reasoning ability. Pre-requisite tests used Lilliefors method for normality test and Bartlett method for homogeneity test. After examining the data, it shows that the populations have same variance and they were in normal distribution. Prior knowledge data were examined by using one-way analysis of variance with unbalanced cells. Hypothesis was examined by using two-way analysis of variance with unbalance cells followed multiple comparative test using Scheffe method. The result of the research showed as follows. (1) Problem Posing model type within solution posing gave better achievement than Problem Posing type Pre Solution Posing, type post Solution Posing and direct learning model, whereas Problem Posing model type Pre Solution Posing gave better achievement than Problem Posing type Post solution Posing and direct learning model. Meanwhile, Problem Posing model type Post Solution Posing gave better achievement than learning direct model. (2) Students who had high reasoning ability got better achievement than students who had medium or low reasoning ability, whereas students who had medium reasoning ability, got better achievement than students who had low reasoning ability.(3) in every learning model, students who had high reasoning ability got better achievement than students having medium or low reasoning ability. Meanwhile, students who had medium reasoning ability got better achievement than students who had low reasoning ability. (4) In every category of reasoning ability Problem Posing model type within solution posing gave better achievement than Problem Posing type Pre Solution Posing, type Post Solution Posing and direct learning model, whereas Problem Posing model type Pre Solution Posing gave better achievement than Problem Posing type Post solution Posing and direct learning model. Meanwhile, Problem Posing model type Post Solution Posing gave better achievement than direct learning model.Keyword: Problem Posing Type: Within Solution Posing, Pre Solution Posing, Post Solution Posing, mathematic achievement, and reasoning ability.